Relationship between basketball free-throw accuracy and other performance variables among collegiate female players - Mana Ogawa; Satoko Hoshino; Motoko Fujiwara; Hiroki Nakata (Japanese Society of Physical Fitness and Sports Medicine, 2019)
We investigated the relationship between basketball free-throw accuracy and anthropometry, physical fitness tests, and performance variables among 16 collegiate female basketball players. Each participant performed 20 basketball free throws. Anthropometric measures were height and weight; physical fitness tests were sit-and-reach, back strength, and grip strengths; other basketball performance variables were the phases of the pre-shoot routine: (a) time taken, (b) minimum angle when taking the ball back, (c) angle at ball release, (d) angular displacement during the forward arm swing, and (e) angular velocity at ball release on the elbow, shoulder, hip, knee, and ankle. We analyzed the correlation between free-throw accuracy and data on anthropometry and physical fitness, the time period and variability of the pre-shot routine, and kinematic data. There were negative correlations between free-throw accuracy and mean pre-shot time, and variability of the pre-shot time, indicating that participants with a shorter and less variable pre-shot time showed a higher free-throw accuracy. Angular displacement of the shoulder during the forward swing and angular velocity of the knee at ball release showed positive correlations with free-throw accuracy. There was also a negative correlation between free-throw accuracy and variability of angular displacement during the forward swing at the elbow, indicating that participants with smaller variability of angular displacement of the elbow showed higher free-throw accuracy. Some performance variables, including routine duration, angular displacement of the shoulder and elbow, and angular velocity of the knee, were related to free-throw accuracy.